Unravelling the Surface Oxidation-Induced Evolution of the Electronic Structure of Gallium - Hsieh, Tzung En; Frisch, Johannes; Wilks, Regan G.; Bär, Marcus (ACS Applied Materials and Interfaces, 2023)
Gallium is widely used in liquid metal catalyst fabrication, and its oxidized species is a well-known dielectric material. In the past decades, these two species have been well studied separately. However, the surface oxide layer-induced impact on the chemical and electronic structure of (liquid) gallium is still mostly unclear because of the extreme fast formation of thermodynamically stable surface Ga2O3. In this study, we used a combination of direct and inverse photoemission complemented by scanning electron microscopy to examine the surface properties of Ga and Ga oxide (on a SiOx/Si support) and the evolution of the surface structure upon stepwise oxidation and subsequent reduction at an elevated temperature. We find oxidation time-dependent self-limited formation of a substoichiometric Ga2O3−δ surface layer on the Ga nanoparticles. The valence band maximum (conduction band minimum) for this Ga2O3−δ is located at −3.8 (±0.1) eV [1.4 (±0.2) eV] with respect to the Fermi level, resulting in an electronic surface band gap of 5.2 (±0.2) eV. Upon annealing in ultrahigh vacuum conditions, the Ga2O3−δ surface layer can efficiently be removed when using temperatures of 600 °C and higher. This study reveals how the surface properties of Ga nanoparticles are influenced by stepwise oxidation-reduction, providing detailed insights that will benefit the optimization of this material class for different applications.
CRIS-Team Scopus Importer:2023-11-03
Keywords: conduction band minimum; gallium; gallium oxide; IPES; PES; valence band maximum